Overcoming physiological dormancy in eucommia ulmoides seeds: roles of scarification, stratification, and hormonal treatments (Bangladesh Journal of Botany, 2025)
Eucommia ulmoides is endemic to China and has great development and utilization prospects. Seed dormancy is the main obstacles to the effective propagation of Eucommia ulmoides Oliv. The study investigated strategies for breaking dormancy and enhancing germination by evaluating the effects of scarification, cold stratification, gibberellic acid (GA3), and their combined application at various temperatures. Results showed that the seeds do not have a barrier to water absorption, layers of palisade cells were not found in seeds, the intact seeds germinated at an optimum temperature with a low germination percentage of 5%, scarification can release seed dormancy and stratification and gibberellic acid can also break seed dormancy 15°C was the optimum temperature for seed germination.  These findings demonstrated that E. ulmoides seeds exhibited physiological dormancy (PD) by scarification and stratification with GA3 application.Bangladesh J. Bot. 54(4): 901-911, 2025 (December)